2017
DOI: 10.1016/j.ijpharm.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide-coated liposomal formulations for dental targeting

Abstract: The efficacy of treatments of oral ailments is often challenged by a low residence time of the conventional pharmaceutical formulations in the oral cavity, which could be improved by using bioadhesive formulations. This in vitro study investigated charged liposomes, both uncoated and coated through electrostatic deposition with polysaccharides (chitosan, alginate and pectin), as bioadhesive systems for the oral cavity. First, formulations that provided liposomes fully coated with polysaccharide were selected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…6 (for K2-loaded nanoliposomes). In general no aggregation among nanoliposomal structures (both uncoated and chitosan-coated) was observed, in agreement with the results obtained by, 39 demonstrating that negatively charged polysaccharide coated liposomes had more stability against aggregation.…”
Section: Encapsulation Efficiencysupporting
confidence: 90%
“…6 (for K2-loaded nanoliposomes). In general no aggregation among nanoliposomal structures (both uncoated and chitosan-coated) was observed, in agreement with the results obtained by, 39 demonstrating that negatively charged polysaccharide coated liposomes had more stability against aggregation.…”
Section: Encapsulation Efficiencysupporting
confidence: 90%
“…In fact, the use of charged liposomes, either uncoated or coated using electrostatic deposition with polysaccharides (alginate, chitosan and pectin), as bioadhesive systems for the oral cavity was investigated through an in vitro study ( Fig. 2 ) [23] . It was found that the liposome surface charge was highly important for their stability in saliva and for bioadhesion.…”
Section: Classification Of Pmfs In Dentistrymentioning
confidence: 99%
“…It was found that the liposome surface charge was highly important for their stability in saliva and for bioadhesion. The negatively charged liposomes were the most stable in artificial saliva, and the stability of the positively charged liposomes in the film was improved using a negatively charged polysaccharide [23] .
Fig.
…”
Section: Classification Of Pmfs In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the stability, both in vivo and in vitro, liposomes have been coated with polymers [10][11][12]. The polymers forming the coating may be attached to the liposomal surface by electrostatic deposition, e.g., chitosan [10,13,14], pectin [15,16], poly(N-isopropylacrylamide (PNIPAAM)-comethacrylic acid) [17], and alginate [18]. Charged polymer coatings have also been introduced for improving the mucoadhesive properties of the system [19][20][21] and for formulation of pH sensitive [22] and temperature sensitive delivery systems [23].…”
Section: Introductionmentioning
confidence: 99%